2014
DOI: 10.1007/s13277-014-2337-7
|View full text |Cite
|
Sign up to set email alerts
|

Fucoxanthin induces apoptosis in human cervical cancer cell line HeLa via PI3K/Akt pathway

Abstract: Cervical cancer (CC) is a malignant neoplasm arising from cells originating in the cervix uteri, among the top causes of death from cancer in women. In a gene expression profiling study of metabolic response to treatment, PI3K/Akt signaling pathway are associated with the development of CC. A common mechanism of Akt activation seen in cancer types is alterations in the upstream regulators of Akt such as phosphatidylinositol 3-kinase (PI3K), which is overexpressed in cervical cancer tissues, and leads to phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…These results demonstrate that CrkL may promote cervical cancer cell invasion through activation of Src signaling pathways. In addition, CrkL was also found to promote Akt phosphorylation; Akt signaling activation has been reported to be involved in the chemoresistance of cancer cells through antiapoptotic proteins such as Bcl-2 and Bcl-xL (36,37). Thus it is possible that CrkL increases cervical cancer chemoresistance through activating Akt signaling.…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrate that CrkL may promote cervical cancer cell invasion through activation of Src signaling pathways. In addition, CrkL was also found to promote Akt phosphorylation; Akt signaling activation has been reported to be involved in the chemoresistance of cancer cells through antiapoptotic proteins such as Bcl-2 and Bcl-xL (36,37). Thus it is possible that CrkL increases cervical cancer chemoresistance through activating Akt signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Ganesan et al showed that 10 μM of fucoxanthin caused apoptosis and caspase-3 activation in HL-60 cells (29). Fucoxanthin (0.5 μM) was shown to induce caspase-dependent apoptosis with an increase in BAX and reduction in BCL2, phosphatidylinositol-3-kinase (PI3K) and a phosphorylated form of AKT in HeLa cells (30). The authors also found NF-ĸB inactivation and a decrease in its translocation to the nucleus from the cytoplasm in cells treated with fucoxanthin.…”
Section: Fucoxanthin Inhibits Tumor Cell Growth By Inducing G 1 Cell-mentioning
confidence: 99%
“…Interestingly, fucoxanthin and its metabolite fucoxanthinol exhibit few adverse effects on normal, uninfected cells both in vitro and in vivo (Yamamoto et al, 2011). Extensive studies have been carried out regarding the separation, purifi cation, bioavailability, and biological activity of fucoxanthin from macroalgae (Wang et al, 2005;Yang et al, 2008;Fung et al, 2013;Molina et al, 2014;Ye et al, 2014). However, the fucoxanthin content in macroalgae is very low, requiring complex processes for purifi cation and high production costs.…”
Section: Introductionmentioning
confidence: 99%